THE TRANSFORMATION OF QUR'AN INTERPRETATION AND THE DYNAMICS OF TEXT AUTHORITY IN INDONESIA A CRITICAL ANALYSIS - Zulliandi, Yuviandze Bafri; Intan Wulansari; Nurul Aulia (Universitas Kiai Abdullah Faqih Gresik, 2025)
The study of Quranic exegesis (tafsir) in Indonesia has undergone a significant transformation, reflecting the dynamic interplay between textual authority and socio-cultural contexts. The transformation of tafsir in Indonesia is not merely a scholarly pursuit, but also a reflection of the broader socio-political and cultural landscapes that shape the interpretation of the sacred text. This transformation is evident in the various approaches to tafsir, ranging from traditional methods to modern contextual analyses, which reveal the underlying epistemological frameworks and ideological stances of the interpreters. This research employs a qualitative approach with critical analysis to explore the evolution of interpretative authority and the shifts in hermeneutical strategies within the Indonesian context. The study concludes that the dynamics of Quranic textual authority in Indonesia are the result of a complex interaction between tradition, innovation, and socio-political forces.